Avaliação da vida de prateleira de peito de frango sem pele sob refrigeração - Moura, Marcio Fernando Ducat (2011)
The shelf life of foods is the time allowed for food to be consumed safely on the microbiological aspects, physicochemical and sensory characteristics, and is a determining factor in production logistics, trade and consumption, considered in the cost of the product, especially when it comes to perishable foods, for the presence and growth of micro-organisms during production to consumption are inevitable and their study is essential for the development of conservation technologies as well as determining with regard to the risk which consumers are exposed to. In this work we simulated the conditions of time (fifteen days) and temperature (<2.0 ° C) as indicated by the manufacturer shelf life of the product analyzed and the evaluations performed microbiological and physico-chemical properties during times of 0, 5, 10 and 15 days for raw and under cooling (1.4 ± 0.6 ° C) chicken breast without skin. The samples were analyzed for the presence / absence of the microorganism Salmonella spp., quantification of mesophilic microorganisms, MPN- most probable number for the group of coliform bacteria, the presence / absence of the Escherichia coli and pH analysis. None of the samples showed the presence of Salmonella spp. during the study , however, 10 days time was the limit for guaranteeing the quality of the microorganism Fecal samples at 45 ° C, and 70% of samples unfit for human consumption and at odds with the precepts of sanitary legislation in force. It was found that the microbiological quality of chicken flesh had flaws, as demonstrated by the high number of mesophilic aerobic bacteria, coliforms at 35 ° C and the confirmed presence of E. coli in 20% of the samples, which may therefore be a potential risk for the occurrence of foodborne illnesses DVA.